2022
DOI: 10.1002/hed.27162
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic outcomes of salvage surgery and immune checkpoint inhibitor therapy in recurrent head and neck squamous cell carcinoma: A single‐institution retrospective study

Abstract: Background Survival outcomes in recurrent head and neck squamous cell carcinoma (HNSCC) are poor. This study aimed to compare survival outcomes between salvage surgery and immunotherapy in patients with recurrent advanced HNSCC. Methods Patients with advanced stage (stage III or IV) recurrent HNSCC following treatment with platinum‐based chemotherapy were included. Survival was estimated using the Kaplan–Meier method, and Cox regression was used for multivariate logistic regression. Results Two‐year overall su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(57 reference statements)
1
3
0
Order By: Relevance
“…Membrane GO MF was mainly enriched in receptor ligand activity, carbohydrate binding, and the following cytokine activity KEGG pathway: neuroactive ligand-receptor interaction. These results suggest that the main differences between the high- and low-risk groups are immune-related, which was consistent with previous results ( Yuan et al, 2022b ; Konuthula et al, 2022 ). Therefore, we further performed a CIBERSORT immune infiltration analysis, which showed that the differential gene expression levels of the 25 relevant inflammatory factors were associated with immune function and increased the risk scores.…”
Section: Discussionsupporting
confidence: 93%
“…Membrane GO MF was mainly enriched in receptor ligand activity, carbohydrate binding, and the following cytokine activity KEGG pathway: neuroactive ligand-receptor interaction. These results suggest that the main differences between the high- and low-risk groups are immune-related, which was consistent with previous results ( Yuan et al, 2022b ; Konuthula et al, 2022 ). Therefore, we further performed a CIBERSORT immune infiltration analysis, which showed that the differential gene expression levels of the 25 relevant inflammatory factors were associated with immune function and increased the risk scores.…”
Section: Discussionsupporting
confidence: 93%
“…However, this is the largest study to our knowledge that investigates the predictive significance of CCI in patients with stage IV HNC receiving treatment with immunotherapies in particular. In a retrospective analysis of patients with advanced stage recurrent HNC treated with immunotherapy, Konuthula et al found CCI score to not be predictive of OS; however, this analysis was limited by a small sample size ( N = 44) 17 . Further research is needed to confirm these findings for other stages of HNC disease.…”
Section: Discussionmentioning
confidence: 91%
“…In a retrospective analysis of patients with advanced stage recurrent HNC treated with immunotherapy, Konuthula et al found CCI score to not be predictive of OS; however, this analysis was limited by a small sample size (N = 44). 17 Further research is needed to confirm these findings for other stages of HNC disease.…”
Section: Discussionmentioning
confidence: 95%
“…In a first of its kind analysis, implementing a single-institution retrospective study design, Konuthula and colleagues compared oncologic outcomes of salvage surgery and ICI therapy as first line treatment in patients with recurrent HNSCC without distant metastasis who failed primary chemoradiotherapy ( 13 ). In their cohort, 2-year overall survival for patients who underwent salvage surgery was 69%, but only 25% in those who received ICI immunotherapy.…”
Section: Introductionmentioning
confidence: 99%